2014
DOI: 10.3233/rnn-140404
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cells improve recovery in stroke-injured aged rats

Abstract: Purpose: Induced pluripotent stem cells (iPSCs) improve behavior and form neurons after implantation into the stroke-injured adult rodent brain. How the aged brain responds to grafted iPSCs is unknown. We determined survival and differentiation of grafted human fibroblast-derived iPSCs and their ability to improve recovery in aged rats after stroke. Methods: Twenty-four months old rats were subjected to 30 min distal middle cerebral artery occlusion causing neocortical damage. After 48 h, animals were transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 47 publications
0
58
0
Order By: Relevance
“…When considering the overall results of the behavioral tests performed after iPSC transplantation after stroke, improvements in general neurological score, 169 motor, 57,58,164,169,170 sensorimotor, 57,58,164,169,170 and cognitive function 164 were observed. On the contrary, Jensen et al did not observe an iPSC-mediated improvement in behavioral function.…”
Section: B Neurogenic Predifferentiated Ipscs In In Vivo Stroke Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the overall results of the behavioral tests performed after iPSC transplantation after stroke, improvements in general neurological score, 169 motor, 57,58,164,169,170 sensorimotor, 57,58,164,169,170 and cognitive function 164 were observed. On the contrary, Jensen et al did not observe an iPSC-mediated improvement in behavioral function.…”
Section: B Neurogenic Predifferentiated Ipscs In In Vivo Stroke Modelsmentioning
confidence: 99%
“…On the contrary, Jensen et al did not observe an iPSC-mediated improvement in behavioral function. 171 The underlying mechanisms of action of the transplanted iPSCs include migration and local neuronal maturation of the transplanted iPSCs, 57,58,164,170 synaptic integration into the host brain 57, 58 but also paracrine effects of the donor cells are considered to play a role. 169 The transplanted iPSCs were predifferentiated toward long-term expandable neuroepithelial-like stem cells, 57,58,170 fated toward cortical neurons 57 or toward neuronal precursor cells.…”
Section: B Neurogenic Predifferentiated Ipscs In In Vivo Stroke Modelsmentioning
confidence: 99%
“…As of now, while work by Jensen et al reported no iPSC-mediated improvement in behavioral function in stroke (Jensen et al, 2013), several others, as previously mentioned, show that also direct iPSC transplantation improves neurological score, motor, sensory and cognitive functions, already within the first week after transplantation, when migration, maturation, synaptic integration, and paracrine release into the host brain is completed (Oki et al, 2012; Polentes et al, 2012; Tornero et al, 2013, 2017; Yuan et al, 2013; Tatarishvili et al, 2014). …”
Section: How Do Neural Precursors From Induced Pluripotent Stem Cellsmentioning
confidence: 93%
“…These PAX6+ dorsal forebrain progenitors present a neural population that conveniently aligns with the common stroke models that induce infarcts within the cortex. Following transplantation, these PSC-derived neurons exhibit a remarkable capacity for longdistance anatomical integration and establishment of appropriate electrophysiological properties (Denham et al, 2012;Espuny-Camacho et al, 2013;Niclis et al, 2017c) and, similar to fetal and adult NSC grafts, provide varying degrees of functional recovery (Chan-Ling et al, 2008;Jiang et al, 2011;Gomi et al, 2012;Oki et al, 2012;Jensen et al, 2013;Qin et al, 2013;Tornero et al, 2013;Tatarishvili et al, 2014). Behavioural recovery, however, has commonly been observed over timeframes inconsistent with the maturity of implanted human neurons, thereby making it difficult to assess the direct contribution of these cells to neuronal replacement.…”
Section: Figurementioning
confidence: 99%